ROLE OF GREENTEA IN CANCER PREVENTION - Arintha Devi, Cok Istri; Ika Wahyuniari, Ida Ayu (E-Jurnal Medika Udayana; vol 2 no4 (2013):e-jurnal medika udayana)
Cancer is one of deadliest disease in developed or developing country. Most of the cancer which had metastase can not be cured. Based on this statement, the one most effective way to prevent cancer is to prevent the cancer progression itself. This is called  chemoprevention . The concept of chemoprevention is to control cancer by slowing its growth and progression. One of the simplest and cheapest chemopreventive is by consume greentea everyday. Greentea contain antioxidant which can prevent the oxidative stress. Greentea also have role to prevent oxidation and reduction reaction, promote apoptosis, detoxification of carcinogen, dan prevent signaling for cancer hyperproliferation.
Keywords: greentea, antioxidant, cancer prevention